Effects of enteral nutrition method using continuous feeding on patients in intensive care: A Systematic Review - Gatra Satria; Debie Dahlia; Dikha Ayu Kurnia; Agung Waluyo (AcTion: Aceh Nutrition Journal, 2024)
Patients treated with intensive care are at risk of malnutrition. Enteral nutrition can help to maintain a patient's nutritional needs and digestive system function. However, some complications are associated with enteral feeding, including aspiration and refeeding syndromes. This study aimed to provide a comprehensive synthesis of the effects of enteral feeding methods in Intensive Care Unit (ICU) patients. Related literature was systematically retrieved from 2019 to 2023 using the ProQuest, PubMed, Clinical Key, Science Direct, and Cochrane Library databases. Specific keyword combinations were applied when searching only for randomized controlled trials (RCT) on enteral feeding in critically ill patients. The results of this study found six articles were selected after screening based on the inclusion criteria. The continuous feeding method was found to improve the achievement of the target nutritional requirements and reduce the risk of aspiration. However, it is not always appropriate to consider circadian rhythm. In conclusion, there are important clinical factors to be considered before selecting the type of enteral access, including the patient’s clinical condition, surgical history, length of anticipated feeding time, and potential risks.